Oil Spill in a Marine Environment: Requirements Following an Offshore Oil Spill (Rudarsko-geološko-naftni zbornik, 2021)
The global lifestyle of this modern world has become more dependent on petroleum-based products, whose applications are involved almost everywhere. Since a large quantity of oil is being used on a daily basis, the spilling of oil by various means during its storage and transportation has become inevitable. This work focuses on the spilling of oil in a marine environment, generally referred to as an offshore oil spill, in contrast to an onshore oil spill associated with a terrestrial environment. These oil spills not only devastate the natural resources and unsettle the economy, they also jeopardize marine life, as well as human health. The remediation of an oil spill remains very challenging, when the disaster is associated with a large aerial extent. In this context, a sound understanding is required on the origin, seeping, composition and properties of the spilled oil in order to better monitor the spreading of the oil spill. In this manuscript, a detailed list of fundamental queries, which will be required to be addressed at the instance of an oil spill has been deduced, which will be extremely useful for the oil spill respondents as there are no previous studies that exclusively provide the type and nature of data required to be collected, immediately following an oil spill. Furthermore, this manuscript has deduced a list of sensitive and essential plots that will be required in order to analyse and forecast the spreading of an oil spill. An essence of weathering and its associated movement of oil spill has been included.